2013
DOI: 10.1557/jmr.2013.340
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically driven selective growth of InAs quantum dots on GaAs

Abstract: We show that, by changing and tuning the direction of the As flux on a rippled substrate, at temperatures higher than 530 degrees C and high As/In flux ratio, a selective growth of InAs dots can be obtained on GaAs. This is an undisclosed effect related to the Arsenic flux in the molecular beam epitaxial growth of InAs quantum dots (QDs) on GaAs(001). This effect cannot be explained by a shadowing effect, due to the gentle slopes of the mounds (1-3 degrees), and reveals instead that As plays a fundamental role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The small As flux difference (DF/F % 4%) on the two sides of the mounds due to the fixed As beam direction, together with the high mobility of In cations at high temperature, cause a current of In adatoms from the side less exposed to the side more exposed to the As flux. We have found that the dots nucleating on the mound side opposite the direction of the As flux tend to dissolve 11,21 and their material move to the other side in a sort of ripening effect. 22,23 To explain the vertical stacking of dots, shown in Fig.…”
mentioning
confidence: 86%
“…The small As flux difference (DF/F % 4%) on the two sides of the mounds due to the fixed As beam direction, together with the high mobility of In cations at high temperature, cause a current of In adatoms from the side less exposed to the side more exposed to the As flux. We have found that the dots nucleating on the mound side opposite the direction of the As flux tend to dissolve 11,21 and their material move to the other side in a sort of ripening effect. 22,23 To explain the vertical stacking of dots, shown in Fig.…”
mentioning
confidence: 86%
“…In previous reports 13, 14 we discussed the main mechanisms responsible for the selective growth and pointed out that the samples grown in CD mode showed only a poor selective growth. However, in light of the kinetic processes identified by our model, 13 we expect that a consistent reduction of the growth rate should enhance the selective growth in the CD mode as well.…”
Section: Resultsmentioning
confidence: 90%
“…1d) since the As flux gradient, due to the oblique evaporation, is responsible for an In-adatoms drift current over the surface which determines the position where the QDs grow, provided the growth temperature is sufficiently high to enhance the In surface mobility. 13,14 The comparison between CD and PD samples in Fig. 1 clearly shows that, by progressively reducing the growth rate to 1/6 with respect to the one used in the PD growth (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We have recently shown that, when the InAs is deposited with the sample rotation off and with an oblique orientation of the As 4 flux with respect to the (110) plane of the sample, the QDs align along the step bunching of one single side of the mounds (right panel of figure ). We showed that the mound side where the QDs are located is determined by the direction of the impinging As 4 beam.…”
Section: Resultsmentioning
confidence: 99%